1993
DOI: 10.1055/s-0038-1649570
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of α2-Antiplasmin and Plasminogen Activator Inhibitor 1 (PAI-1) in the Inhibition of Clot Lysis

Abstract: SummaryThe relative importance of the two major inhibitors of fibrinolysis, α2-antiplasmin (α2-AP) and plasminogen activator inhibitor (PAI-1), were investigated using a simple microtitre plate system to study fibrin clot lysis in vitro. Cross-linked fibrin clots contained plasminogen and tissue plasminogen activator (t-PA) at concentrations close to physiological. Purified α2-AP and PAI-1 caused dose-dependent inhibition. All the inhibition due to normal plasma, either platelet-rich or poor, was neutralised o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 22 publications
2
57
1
Order By: Relevance
“…We subsequently showed that, in the marrow of normal individuals, there were significant amounts of t-PA activity present, whereas in the marrow from patients with acute myeloid leukaemia, the PA was not t-PA, but u-PA (McWilliam et al, 1996(McWilliam et al, , 1998. Scherrer et al (1999) have recently shown that blast cells in acute myeloid leukaemia contain mRNAs for not only u-PA, but, in some types, for u-PAR, PAI-1 and PAI-2 also. None of the above studies, although they detected u-PA, directly examined the ability of leukaemic cells to lyse fibrin deposits, as they all depended upon ex vivo manipulation of the blood to separate plasminogen activators from their inhibitors prior to demonstrating the activity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We subsequently showed that, in the marrow of normal individuals, there were significant amounts of t-PA activity present, whereas in the marrow from patients with acute myeloid leukaemia, the PA was not t-PA, but u-PA (McWilliam et al, 1996(McWilliam et al, , 1998. Scherrer et al (1999) have recently shown that blast cells in acute myeloid leukaemia contain mRNAs for not only u-PA, but, in some types, for u-PAR, PAI-1 and PAI-2 also. None of the above studies, although they detected u-PA, directly examined the ability of leukaemic cells to lyse fibrin deposits, as they all depended upon ex vivo manipulation of the blood to separate plasminogen activators from their inhibitors prior to demonstrating the activity.…”
Section: Discussionmentioning
confidence: 93%
“…It has subsequently been demonstrated that normal bone marrow possesses considerable plasminogen-activating activity, largely because of t-PA (McWilliam et al, 1996), whereas marrow from patients with myeloid forms of acute leukaemia contains u-PA detectable both functionally and immunologically (McWilliam et al, 1998). Scherrer et al (1999) have confirmed the finding of u-PA antigen in leukaemic cells and have shown that they contain the u-PA receptor, u-PAR, in addition. The present study was undertaken to determine whether leukaemic blast cells contain sufficient quantities of plasminogen activator themselves to produce lysis of fibrin, and whether this is a property of APL blasts alone or is also present in other myeloid or non-myeloid forms of leukaemia.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Human fibrinogen (FGN) was from Sigma (St. Louis, MO). Human plasminogen (PLG) was isolated from plasma (Stewart Regional Blood Center, Tyler, TX) using affinity chromatography on lysine-sepharose 4B beads [19]. The PLG preparation was homogenous and appeared on a Coomassie-stained gel as a doublet with apparent molecular weights corresponding to Glu-and Lys-forms of PLG, confirming that the preparation was highly purified and consisted of these two forms.…”
Section: Reagentsmentioning
confidence: 96%
“…This effect is enhanced if the clot is protected from tissue plasminogen activatorinduced fibrinolysis. In several studies it has been shown that PAI-1 protects fibrin clots from tPA-mediated plasmin degradation in a dose-dependent manner (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%